International carbon emissions trading and strategic incentives to subsidize green energy - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2010)
This paper examines strategic incentives to subsidize green energy in a group of countries that operates an international carbon emissions trading scheme. Welfare-maximizing national governments have the option to discriminate against energy from fossil fuels by subsidizing green energy, although in our model green energy promotion is not efficiency enhancing. The cases of small and large countries turn out to exhibit significantly differences. While small countries refrain from subsidizing green energy and thus implement the efficient allocation, large permit-importing countries subsidize green energy in order to influence the permit price in their favor.
Keywords: H21; Q42; Q48; 330; emissions trading; black energy; green energy; energy subsidies; Förderung regenerativer Energien; Strategische Handelspolitik; Kohlendioxid; Emissionshandel; International; Landesgröße; Theorie